ADVERTISING CAMPAIGNS IN TV CHANNELS : (A Research Drawn from A Master Thesis) - Hameed al-Dulaymi, Abd al-Satar (ALBAHITH ALALAMI, 2022)
Television culture has become the most dangerous of our time. It manipulates with minds and hearts together; and forms consciousness. It transforms societies into actual forces rejecting certain principles by guiding the media landscape through visible connotations acceptable to the public; or provokes the citizen against elements that put a burden on the viewer or the public in order to create a positive reaction to the subject of combating terrorism by combining these ads in line with what the public wants of security and tranquility and a decent living after suffering from terrorism in the past years. Therefore, this research deals with television advertisements as one of the most important forms of media which display advertisements on terrorism; renounce violence; create awareness and peaceful coexistence among the Iraqi people; enlighten the minds to the suffering caused by terrorism and create a public opinion through emotional and mental uses. How the public dealt with it and what kind of impact it had on the general population. Are the reactions positive or negative? Thus, the requirements of the research required to be divided into two searches, the first of which titled (advertising campaigns: types and methods), while the second was under the title (characteristics of television as an advertising medium). This research dealt with advertising campaigns, definition and concept; and planning of advertising campaigns and their objectives; types of campaigns and functions of advertising communication; and evaluation of advertising campaigns and their relationship to other communication patterns. While the second section addressed (the characteristics of television as a means of advertising) which referred to the types of television advertising and formats of editing methods; as well as ethics broadcasting and advertising industry in television channels.